Analisis Kritis Liturgi Perjamuan Kudus Huria Kristen Batak Protestan - Binsar Jonathan Pakpahan (Indonesian Journal of Theology, 2014)
The liturgy of the Eucharist is a communal rite that becomes a very important foundation of the theological construction of the church. The church must have a good foundation of the Eucharist as a place where they can encounter God as a community. As a result, the theology that comes from this encounter will encourage the church to act out in her theology in the world. In 2014, Huria Kristen Batak Protestan (Protestant Batak Christian Church/HKBP) is trying to reformulate their church order. This research encourages HKBP to look at their theology of the Eucharist more seriously. By using a critical analysis towards the HKBP liturgy of the Eucharist, this paper shows the inconsistency between the HKBP church documents view on the Eucharist. The inconsistency is caused by the different times of the writing of the documents, which were never synchronized.